Melt inclusions at MT. Edixon (Antarctica): Chemistry, petrology and implications for the evolution of the Lanterman range - Ferri F.; Cesare B.; Bartoli O.; Ferrero S.; Palmeri R.; Remusat L.; Poli S. (Lithos, 2020)
The recovery of melt inclusions (MI) in peritectic phases of metamorphic rocks demonstrates their anatectic origin even in the absence of other textural or field evidences, and gives the opportunity to retrieve the chemical composition of primary melts and infer melt entrapment conditions. Here we report the first recovery of such inclusions in a medium-grade schist from the Edixon Metamorphic Complex (EMC) of the Lanterman Range in northern Victoria Land, Antarctica. This is the first study of melt inclusions from an Al2SiO5-free, graywacke-type protolith. Inclusions are hosted in garnet. They are both polycrystalline nanogranitoids, i.e., crystallized former MI, and fluid inclusions (FI) coexisting in the same clusters and displaying frequent negative crystal shape and textures indicative of a primary origin. The MI contain albite, K-feldspar, quartz, muscovite, biotite ± calcite ± siderite ± H2O, while the FI are composed by CO2 + H2O + N2 + CH4 ± H2S and contain step-daughter calcite. The schist hosting the garnets with melt inclusions contains muscovite, biotite, garnet, plagioclase, K-feldspar, and quartz. Extensive resorption of garnet and replacement by biotite, along with composition of micas that suggest medium-temperature, subsolidus conditions, indicate that after anatexis the schist was thoroughly recrystallized under retrograde conditions. The MI were remelted in a piston cylinder apparatus at conditions of 740–900 °C at 0.8–1.0 GPa with complete remelting taking place at 760–780 °C. The remelted glass is sub-alkaline, peraluminous (ASI ≈ 1.3–1.5) with CaO ≈ 1.2–2.1 wt% and K2O ≈ 3.4–4.1 wt% and contains ≈ 4.3–5.3 wt% of H2O and 400–1150 ppm of CO2. The P-T conditions of melt entrapment were retrieved combining results of experimental remelting with calculated phase equilibria in the MnCNKFMASHT model system, and are between 740 and 780 °C and 0.7 to 0.9 GPa. The new and different P-T conditions for a high grade rock of the EMC with respect to other published data, confirm that this metamorphic ...